Elastic moduli and hardness of η-Ta2N3 from nanoindentation measurements. (July 2015) - Bourguille, Judith; Brinza, Ovidiu; Tétard, Florent; Nikitin, Sergey; Zerr, Andreas
Abstract Nanoindentation testing was used to determine elastic moduli and hardness of η-Ta2N3, a novel stiff and hard high-pressure compound recoverable at ambient conditions. For a sample having porosity of 14% we confirmed densification of its upper layer induced by mechanical polishing: At depths <?CDATA ${<}400\ \text{nm}$ ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7s4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> we obtained <?CDATA ${{\sim}10{%}}$ ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7pg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> higher reduced elastic modulus <?CDATA $E_{r}$ ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7mc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and <?CDATA ${{\sim}25{%}}$ ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7kt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> higher hardness when compared with the sample without the densified layer. Using the experimental values of <?CDATA $E_{r}= 238\ \text{GPa}$ ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7j8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and of porosity we derived the shear modulus of dense η-Ta2N3 to be <?CDATA $G_{0}=124\text{-}144\ \text{GPa}$ ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7hq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. Hardness of the porous η-Ta2N3 was measured to be 18 GPa and its fracture toughness estimated to exceed <?CDATA $3.2\ \text{MPa}· \text{m}^{1/2}$ ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7g5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. The Pugh criterion suggests a high malleability of η-Ta2N3 which could explain the observed surface densification.